Я не виноват! - Винник Лариса (Другой, другие, о других. Детский проект Людмилы Улицкой, 2012)
Экземпляры: аб. (20140722) / Инвентарный номер: 55989 / Цена: / Сис.шифр: 71.04 / Авт.знак: В 48 / ГРНТИ: 13.01 / ББК: 71.04